Profitability of self-consumption solar PV system in Spanish households: A perspective based on European regulations. (November 2020) - Escobar, P.; Martínez, E.; Saenz-Díez, J.C.; Jiménez, E.; Blanco, J.
Abstract: Photovoltaic technology has become a key strategy to achieve the European goal of renewable energy rate. But the photovoltaic market is not uniform in the European Union, with different support policies in each country. These policies, if are stable and suitable over a period, can influence investment decisions and ensure a profitability in the investment. This paper studies the profitability of photovoltaic self-consumption installation in Spanish households with Spanish regulations. To develop this study, the electric consumption profile of houses was considered. The difference in profitability has been analyzed according to the number of members of the household. Furthermore, the impact of the adoption of another type of self-consumption support policy has been analyzed (France, Germany, Italy, Great Britain, and Finland). For this, all incentives have been scaled up to the Spanish price. The result is that all these regulations present significantly better profitability than the Spanish, leading to it being considered that the investments have very positive economic parameters. For instance, the payback period in Spain for households of 1–4 members is 21, 17, 16, and 15 years respectively, while in the worst of the other analyzed countries these values are 13, 11, 10 and 10 years. Highlights: A model was presented which measures the profitability of a self-consumption. The number of household members is very important in the profitability of the investment. Spanish regulation has been analyzed compared with other European regulations. The profitability is significantly worse than in all the other analyzed countries.